Evaluation of Using Semi-Autonomy Features in Mobile Robotic Telepresence Systems - Kisilev, Andrey; Kristoffersson, Annica; Melendez, Francisco; Galindo-Andrades, Cipriano; Loutfi, Amy; González-Jiménez, Antonio Javier; Coradeschi, Silvia (My University, 2015)
Mobile robotic telepresence systems used for social interaction scenarios require that users steer robots in a remote environment. As a consequence, a heavy workload can be put on users if they are unfamiliar with using robotic telepresence units. One way to lessen this workload is to automate certain operations performed during a telepresence session in order to assist remote drivers in navigating the robot in new environments. Such operations include autonomous robot localization and navigation to certain points in the home and automatic docking of the robot to the charging station. In this paper we describe the implementation of such autonomous features along with user evaluation study. The evaluation scenario is focused on the first experience on using the system by novice users. Importantly, that the scenario taken in this study assumed that participants have as little as possible prior information about the system. Four different use-cases were identified from the user behaviour analysis.
Keywords: Robótica; Robotics; Telepresence; Autonomous robot